Destination Development for Spiritual Tourism and Tourist Behavior in Chiang Mai Province - Suravichai, Sarunporn; Namwong, Suwaree (Dusit Thani College Journal, 2020)
The main aim of this study is to investigate tourist behavior and spiritual tourism destination development. To achieve the research aim, three objectives were identified: 1) to study motivation of spiritual tourists in traveling to spiritual tourism destinations. 2) to investigate destination accessibility, including convenience, road safety and guideposts. Moreover, study attitudes of spiritual tourists towards the element of spiritual tourism destination development. 3) to study the development of spiritual tourism. This study was conducted with qualitative research methodology by using in-depth interview technique to collect data from 29 spiritual tourists. The researcher has used accidental sampling selection methods. Afterwards, content analysis was used to analyze data. The results showed that the first objective, motivation of spiritual tourists, can be categorized into 6 factors: to get away from diary routine, to relieve pain, to get self-improvement, to face the loss of a loved one, to learn new things, and to accumulate merit. The second objective, attitudes of spiritual tourists, can be divided into 4 categories: 1) attraction-environment: tranquility, natural, privacy, sanctity of the places, delicious foods respectively, activity places, intended service providers and participants, and homelike places. service-offering attractions: a self-arranged timetable is attractive to temple tourists, whereas planned and varied activities are attractive to resort tourists. 2) facilities-food: tourists pay attention to healthy foods and accommodation, however luxury accommodations are not expected in dharma practice activities because of free-of-charge participation, which are different from other spiritual activities in paid expenses. 3) Accessibility to destination: easy accessibility, convenience, road safety and guideposts are needed by spiritual tourists. 4) Ancillary: from the tourists’ perspective, government cooperation is important in potential development of spiritual tourism destinations in Thailand for promotion and help. From this research, the findings of objective 1 and 2 suggest the development of guidelines in spiritual tourisms for the development of spiritual tourism destinations as follows: 1) Attraction-environment: spiritual tourism Is tourism that focuses on fixing or improving the daily lives of tourists who feel they have a problem, by trying to help tourists with psychological treatment to help them to analyze themselves through meditation. Therefore, if government agencies or private sectors want to develop tourist environments which attract tourists, they should focus on environments that are conducive to tourists to concentrate, have a peaceful mind and stay with the self and the characteristics of the environment that are suitable for such activities, such as having a quiet setting, which tourists have said is important. 2) Facilities-food: because spiritual tourists are tourists who pay attention to health, are important. Therefore, in the development of tourist attractions, government agencies or the private sector should focus on vegetarian food and vegan food. As for accommodation: in the case of spiritual activities in the practice of Dharma, most tourists who come aiming for meditation, include some focus on merit making. They are considered to be a group of tourists who do not expect the luxury of accommodation Therefore, the development should focus on providing only basic facilities such as bedding. 3) Accessibility: Regarding directions for accessing tourist spots in the development of spiritual tourism sites, government agencies or private sectors should focus on easy access convenient travel and non-dangerous road conditions Including having signposts. 4) Ancillary: encourage by using the cooperation of the stakeholders. In other words, developing any type of tourism requires cooperation from many sectors, to help promote awareness. For Spiritual tourism in Chiang Mai, many resorts have an atmosphere that is conducive to spiritual activities. However tourists still carry the image that, If wishing to do spiritual practice, they must go to the temple only. Therefore, the way to develop spiritual tourism in the future If the government helps includes helping to increase awareness of temple or resorts among domestic tourists and foreign tourists. They will help tourists who are looking for spiritual activities to increase awareness and help Thailand earn more from spiritual tourism.